Investigation of mechanical properties in PLA, ABS and epoxy resin parts fabricated by 3D printing technology - Amirhosein Ghaznavi Youvalari; Javad Alizadeh Kaklar; Mahboube Mohamadi (Scientific Reports)
Abstract This study aimed to experimentally investigate the tensile, impact, and fatigue strength of 3D-printed polymers. Tensile and Izod impact tests were conducted on 3D-printed specimens of polylactic acid (PLA), acrylonitrile butadiene styrene (ABS), and epoxy. In the tensile test, PLA, ABS, and epoxy exhibited brittle, tough, and ductile behaviors, respectively. ABS demonstrated the highest impact strength by a significant margin, followed by PLA and epoxy. Subsequently, rotary bending fatigue tests were performed on simple specimens of these polymers under a stress amplitude of 28 MPa. The results indicated that PLA exhibited the highest fatigue life, whereas epoxy demonstrated the lowest. To examine the effect of notches and their geometry on fatigue life, rotary bending fatigue tests were also conducted on notched epoxy specimens featuring circumferential notches and root radii of 1.0, 0.6, and 0.3 mm. Notched epoxy specimens with notch root radii of 1.0 and 0.6 mm exhibited similar fatigue lives, whereas those with a 0.3 mm root radius experienced a fatigue life reduction of approximately one-third. Finite element analysis (FEA) was employed to calculate the maximum von Mises stress at the notch root, demonstrating that the 0.3 mm notch root radius approached a sharp notch and resulted in a substantial effect on stress concentration. Scanning electron microscopy (SEM) was utilized to elucidate the failure mechanisms of the polymers during the impact and fatigue tests.